The use of double-acting cylinders in electro-hydraulic circuit - Duțu, I.C; Axinte, T; Maican, E; Nuțu, C; Diaconu, M (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The paper presents aspects related use of double-acting cylinder. Besides, in the article are presented three hydraulic schemes that double acting cylinder. Meaning, two hydraulic circuits and one electro-hydraulic circuits. First hydraulic schemes has the following devices: fixed displacement pump, air filter, 4/3 way hand lever valve, tanks reservoir, filter and double acting cylinder (Cyli 1-1). However, second hydraulic scheme has the following devices: fixed displacement pump, 4/3 way hand lever valve, check valves, valve office and two double acting cylinders (Cyli 2-1 and Cyli 2-2). Forward, the electro-hydraulic circuit has the following devices: tanks, throttle check valves, 5/2 way hand lever valve, fixed displacement pump, lamp, relays, relay with switch-on delay, valve solenoid and double acting cylinder (Cyli 3-1). The design and simulation of the all three circuits from this article is done FluidSim software from Festo.